Unveiling the Effects of Foreign Exchange Interventions : Evidence from the Kyrgyz Republic - Poghosyan, Tigran (IMF Working Papers; Working Paper, 2020)
This paper analyzes determinants and consequences of FX interventions in the Kyrgyz Republic. Most of the literature on the topic focuses on advanced and emerging economies and this paper provides new evidence from a low-income country. We find that FX interventions take place in response to movements in the exchange rate and its volatility. There is also evidence of 'leaning against the wind', which is more pronounced for relatively larger FX sales and purchases. The 'leaning against the wind' is asymmetric toward FX sales and largely reflects leaning against depreciation of domestic currency. We document a varying degree of de-facto exchange rate stability despite the de-jure floating exchange rate regime. During most of the sample, the exchange rate management index was relatively low in line with the floating exchange rate regime, with the exception of the period from 2018 Q4 until the COVID-19 shock, during which the exchange rate management index was relatively high.